Printable enzyme-embedded materials for methane to methanol conversion - Craig D. Blanchette (Nature Portfolio, 2016)
There is a need for small-scale reactors that convert methane emissions to more valuable products to reduce climate impacts. Here, the authors show that printing 3D structures of the pMMO enzyme enables continuous methane conversion under ambient conditions and reduces mass transfer limitations.